Comparison of Psycho-Social Factors Associated With Suicidal Ideation and Suicide Attempts Among People Living With HIV in Central West China - Wang, Xuelian; Yan, Chuanyuan; Tong, Yongsheng; Gao, Juan; Zhou, Wei; Lan, Zhichao; Wu, Jianlan; Li, Hongbing; Yin, Yi; Wang, Yuehua; Liu, Nancy H.; Deng, Feng (Frontiers in Public Health, 2022)
Background Previous studies have described the correlation of suicidal ideation (SI) or suicide attempts (SA) in people living with HIV (PLWH), whereas few studies compare the correlation between SI and SA in PLWH. Understanding specific risk factors for SI and SA among PLWH will help with developing tailored and effective suicide prevention strategies among this high-risk group. Methods A cross-sectional study was conducted from December 2020 to April 2021 in Baoji municipality, Shaanxi Province. The PLWH registered with the Baoji Municipal Center for Disease Control and Prevention (CDC) were recruited and interviewed. Questionnaires and interviews for this study consisted of socio-demographic variables, mental health history, and psychosocial characteristics. The HIV-related clinical features were obtained from CDC medical records. The PLWH included were divided into three groups, i.e., those with a history of suicide attempts (SA group), those with suicidal ideation only (SI group), and those without any suicidal behavior (NSB group). Multinomial logistic regression was used for three-way comparisons among these three groups of PLWH. Results In total, 995 PLWH were interviewed. The prevalence of probable depression, probable anxiety, SI, and SA in PLWH after being diagnosed as HIV+ was 18.6%, 13.5%, 26.7%, and 3.2%, respectively. Compared with the NSB group, the SI or SA groups were more likely to report probable depression [adjusted odds ratio (AOR) = 2.43, 4.44, respectively], probable anxiety (AOR = 2.80, 5.62, respectively), and high HIV-related stigma (AOR = 2.05, 2.65, respectively). The SI group was more likely to experience high HIV-related stress (AOR = 1.91) and lower quality of life (AOR = 0.56) than the NSB group. Social support and HIV-related clinical features were not associated with SI or SA in this sample. The SA group did not differ from the SI group on any of the psychosocial or HIV-related clinical features. Conclusions Mental health problems are serious in community residents identified with having an HIV infection in a Central West China municipality. It is important to deliver low-cost and effective psychological services tailored for PLWH that are focused on reducing mental health problems. Future studies should utilize sensitive screening measures and further clarify factors potentially associated with the transition from SI to SA in PLWH.